A new species of Crasiella (Gastrotricha: Planodasyidae) from Capron Shoal, Florida, USA - Araújo, Thiago Quintão; Hochberg, Rick (Zootaxa, 2023)
A new gastrotrich species of the genus Crasiella (Macrodasyida: Planodasyidae) is described from Capron Shoal, Florida, USA. The new species is up to 520 μm long and differs from its congeners in the position of adhesive tubes and the structure of its spermatozoa. There are nine TbA that insert ventrally on the head plus an additional pair of TBA that insert medially. Up to 42 TbVL per side. Six pairs of TbP insert on a pair of caudal pedicles. Animals are simultaneous hermaphrodites with an elongated frontal organ and large caudal organ. The spermatozoa have a tripartite acrosome unlike others in the genus that have a four-part acrosome.